PENGARUH VARIASI WAKTU DAN SUHU TERHADAP KEKUATAN TARIK BELT CONVEYOR (2-PLY 1-STEP) PADA PENYAMBUNGAN SISTEM PANAS - Nurman, Ahmad Amril; Syuhri, Ahmad (ROTOR, 2015)
Industry of manufacture continued to increase in line with developments in science and technology. Using belt conveyor to transport materials canât be separated in the industrial world. One of the problems that often occur in conveyor belt is a belt tear or break in the connection. This study aims to determine the best tensile strength in the process of joining belt with hot splicing method, by varying the times (20, 30, 40 minutes) and heating temperature (100, 150, 170 oC) in the process of these connections. The results showed that the best tensile strength is obtained at a temperature of 130 oC and a time of 40 minutes, that is equal to 0.638 MPa.